Virtual aid: a transformation of group mutual aid - Rodriguez-Keyes, Elizabeth; Cormier, Lisa (Journal of Baccalaureate Social Work, 2025)
Keywords: Chemistry; Computer science; Group (periodic table); Mathematics; Mutual aid; Physics; Political science; Pure mathematics; Transformation (genetics); Transformation group; dept.swk

Lessons learned from COVID-19: Being known in online social work classrooms - Smoyer, Amy B; O’Brien, Kyle; Rodriguez-Keyes, Elizabeth (International Social Work, 2020)
This article presents findings from a survey of undergraduate social work (Bachelor of Social Work [BSW]) students about their experiences with remote learning during the 2020 COVID-19 pandemic. In response to this crisis, remote learning was rapidly implemented and many BSW educators and students experienced online classrooms for the first time. Findings from this study shed light on how remote learning shapes the interpersonal relationships and communication that are so critical to building students’ sense of classroom belonging, engagement, and learning.
Keywords: dept.hls; dept.rec; dept.swk; peer-reviewed